Price commitment and the strategic launch of a fighter brand - Peter-J. Jost (Quantitative Marketing and Economics, 2023)
We consider a vertically differentiated market where an incumbent strategically wants to launch a fighter brand to thwart a new entrant. Without a credibly commitment this launch is ineffective because the incumbent always has an incentive to price the fighter brand ex-post out of the market. Endogenous price leadership with fixed or list price announcement, and dual channeling with an intermediary retailer to distribute the fighter brand are analyzed as commitment devices. The optimal mode then depends on customers' sensitivities to a deviation from the price announcement as well as on the attractiveness of the underlying market.
Keywords: 380; Fighter brand; Endogenous price leadership; Dual channeling